Sustainable remediation of vancomycin polluted water using pyrolysis biochar of pressed oil palm fruit fibre - Abiodun Oluwatosin Adeoye; Rukayat Oluwatobiloba Quadri; Olayide Samuel Lawal (Journal of Nigerian Society of Physical Sciences)
Pharmaceutical effluents, especially antibiotics, have significantly contributed to aquatic pollution in recent times, which has called for a sustainable approach to their removal. Adsorption is an efficient process to remove antibiotics from water via the use of materials that could adhere to pollutants and enhance extraction. This study investigated the efficiency of the solid pyrolysis product of pressed palm oil fruit fibre by varying pH and temperature on the removal of vancomycin from water. The following models were used to describe the adsorption kinetics: pseudo-first order, pseudo-second order, Avrami, Elovich, and intraparticle diffusion model, while Temkin, Langmuir, Dubinin Radushkevich (D-R), and Freundlich were used to describe the isotherm. The highest value of the correlation coefficient (R2) of 0.985 was obtained for the pseudo-first order kinetics model. At 40 oC, the correlation coefficients R² were 0.953, 0.995, 0.967, and 0.940 for Temkim, D-R, Langmuir, and Freundlich, respectively. The obtained ranges for standard Gibb’s free energy (Δ Go) > -28.94 kJ/mol and the standard entropy (Δ So) > 0 demonstrate that the adsorption of vancomycin is favourable and spontaneous. The adsorption process was mainly via a physical process, spontaneous and exothermic, since the standard enthalpy (Δ Ho) is -13.92 kJ/mol. The maximum adsorption capacity at 40 oC using the Langmuir isotherm is 3.902 mg/g. The material is a potentially cheap, eco-friendly method for remediating vancomycin from water.